The nonlinear computed torque control of a quadrotor - Y. Meddahi; K. Zemalache Meguenni; H. Aoued (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper work focused on the study of the nonlinear computed torque control of a quadrotor helicopter. In order to model the dynamic of the vehicles, kinematics and dynamics modeling of the X4 is presented. Euler angles and parameters are used in the formulation of this model and the technique of Computed Torque control is introduced. In the second part of the paper, we develop a methodology of control that allows the quadrotor to accomplish a prospecting mission of an environment, as the follow-up of a trajectory by the simulation. Results show that Computed Torque control method is suitable for X4.